The importance and principles of operating of sustaiable geospatial systems in Ukraine today - Semeniuk, Y. O. (ТДАТУ, 2021)
The geospatial profession needs to continually evolve to respond to global challenges, social impacts and the rapid evolution of technology. It is also essential that the next generation of professionals are educated and competent and able to contribute responsibly to the global challenges.
Keywords: land reform; land market